ОФЕ СІЙ НА ПІ ДГОТОВКА МАЙБУТНІХ КЕРІ ВНИКІВ НАВЧАЛЬНИХ ЗАКЛАДІВ ДО ІННОВАЦІЙ НОЇ ЕКОНОМІ ЧНОЇ ДІЯЛ ЬНОСТІ : НАПРЯМ И ДОСЛІ ДЖЕННЯ - Binytska О (Continuing Professional Education: Theory and Practice, 2019)
Theoretical-methodological problems of professional preparation of enterprises managers, establishments and organizations in the field of education and productive studies to conducting innovative economic activity on the modern stage of development of higher education have been analysed in the article. The problem of necessity of future managers professional preparation to conducting innovative economic activity has been reflected